Selective cytotoxicity of green synthesized silver nanoparticles against the MCF-7 tumor cell line and their enhanced antioxidant and antimicrobial properties - Khorrami S (Dove Medical Press, 2018)
Sadegh Khorrami,1 Ali Zarrabi,1 Moj Khaleghi,2 Marziyeh Danaei,3 MR Mozafari3 1Department of Biotechnology, Faculty of Advanced Sciences and Technologies, University of Isfahan, Isfahan, Iran; 2Department of Biology, Faculty of Sciences, Shahid Bahonar University, Kerman, Iran; 3Australasian Nanoscience and Nanotechnology Initiative, Monash University, Clayton, VIC, Australia Introduction: Silver nanoparticles (AgNPs) are of great interest due to their unique and controllable characteristics. Different synthesis methods have been proposed to produce these nanoparticles, which often require elevated temperatures/pressures or toxic solvents. Thus, green synthesis could be a replacement option as a simple, economically viable and environmentally friendly alternative approach for the synthesis of silver nanoparticles.Methods: Here, the potential of the walnut green husk was investigated in the production of silver nanoparticles. An aqueous solution extracted from walnut green husk was used as a reducing agent as well as a stabilizing agent. Then, the synthesized nanoparticles were characterized with respect of their anticancer, antioxidant, and antimicrobial properties. Results: Results showed that the synthesized nanoparticles possessed an average size of 31.4 nm with a Zeta potential of -33.8 mV, indicating high stability. A significant improvement in the cytotoxicity and antioxidant characteristics of the green synthesized Ag nanoparticles against a cancerous cell line was observed in comparison with the walnut green husk extract and a commercial silver nanoparticle (CSN). This could be due to a synergistic effect of the synthesized silver nanoparticles and their biological coating. AgNPs and the extract exhibited 70% and 40% cytotoxicity against MCF-7 cancerous cells, respectively, while CSN caused 56% cell death (at the concentration of 60 µg/mL). It was observed that AgNPs were much less cytotoxic when tested against a noncancerous cell line (L-929) in comparison with the control material (CSN). The free radical scavenging analysis demonstrated profound anti-oxidant activity for the synthesized nanoparticles in comparison with the extract and CSN. It was also detected that the synthesized AgNPs possess antibacterial activity against nosocomial and standard strains of both Gram-positive and Gram-negative bacteria (minimum inhibitory concentration =5–30 µg/mL). Conclusion: These findings imply that the synthesized nanoparticles using green nanotechnology could be an ideal strategy to combat cancer and infectious diseases. Keywords: green synthesis, silver nanoparticles, antimicrobial agent, antioxidant agent, anticancer agent, selective cytotoxicity